2017
DOI: 10.4238/gmr16029550
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the gene eNOS G894T (Glu298Asp) in symptomatic patients with aterosclerosis

Abstract: ABSTRACT. Atherosclerotic and its cardiovascular complications are responsible for 17.5 million deaths a year, according to the World Health Organization. There is consensus that atherosclerosis involves multiple pathogenic processes initiated by endothelial dysfunction, with inflammation and vascular proliferation determining alterations in the matrix, with consequent formation of the atheromatous plaque and its clinical implications. Risk factors such as hypertension, diabetes mellitus, dyslipidemia, and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
6
0
5
Order By: Relevance
“…NO produced by the activity of eNOS modulate, beyond other functions, the degree of constriction experienced by a blood vessel, cell cycle progression, senescence or apoptosis, immune system cells activity and platelet aggregation [51][52][53][54][55]. Moreover, availability of NO influences cancer, genomic stability and cardiovascular diseases [31,39,56,57]. Regarding the p53 protein, which is coded by the TP53 gene, is known as the guardian of the genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO produced by the activity of eNOS modulate, beyond other functions, the degree of constriction experienced by a blood vessel, cell cycle progression, senescence or apoptosis, immune system cells activity and platelet aggregation [51][52][53][54][55]. Moreover, availability of NO influences cancer, genomic stability and cardiovascular diseases [31,39,56,57]. Regarding the p53 protein, which is coded by the TP53 gene, is known as the guardian of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…The eNOS gene regulates the levels of nitric oxide, which is vital for several intracellular biological functions, such as vasodilation, vascular homeostasis, protection of arteries against injuries, cellular growth, signaling pathways and immune response among others [32][33][34][35][36][37]. The eNOS gene has been investigated as a possible biomarker for non-invasive diagnostic and more efficient treatment of cardiovascular diseases [31,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al suggest that eNOS G894T is an important risk factor for IS, specially for LAAS in IS in the North Indian population (24). Furthermore, Campedelli reported that the GG genotype is associated with greater susceptibility to atherosclerosis (30). Moreover, Abdel-Aziz et al recently reported that the TT genotype of eNOS Glu298Asp is an independent risk factor for premature coronary artery disease in Egyptians (31).…”
Section: Discussionmentioning
confidence: 99%
“…TT и GT генотипы были ассоциированы с риском ИБС [36,37] и АГ [38]. Результаты нашего исследования согласуются с исследованием Campedelli с соавт., где наличие GG-генотипа повышало предрасположенность к атеросклерозу [39].…”
Section: результаты и обсуждениеunclassified